The Influence of Examination, Online Registration and Price on Health Services in Hospitals from the Perspective of Don Ihde's Postphenomenology - Elizabeth Nurmiyati Tamatjita (Digital Press Social Sciences and Humanities)
This study adopts a postphenomenological approach based on Don Ihde's thinking to explore the influence of outpatient check-ups, online registration, and price on healthcare in hospitals. With a focus on the interaction between technology and patient experience, this study identifies how online registration facilitates accessibility and efficiency in healthcare, and how outpatient check-ups contribute to positive patient experiences. In addition, price analyses showed an important role in building trust and transparency. The results indicate that these three factors interact with each other to form a positive value for patients, increasing satisfaction and hospital reputation. These findings highlight the importance of considering a phenomenological perspective in designing healthcare services that are responsive to patient needs. Thus, through this approach, Ihde provides a deep insight into how technology plays a role in everyday life and in the broader context of healthcare through four keys namely: Mediation, Empirical Approach, Multiple Relations, Intersubjectivity, and Ontological Shift. The discourse of philosophy of science and knowledge through technology becomes Don Ihde's instrument in understanding the meaning of life, existence and digital human experience. Through the implementation of Ihde's hermeneutics, it is conveyed that it is necessary to understand human interaction with technology which is a technological construction of instruments